(untitled) (Journal of science and technology exploration, 2026)
Against the backdrop of the digital development of smart health, public awareness of health management has continued to increase, and scientific diet has become a core component of national health management and control. Traditional diet management faces problems such as cumbersome recording procedures, delayed nutritional assessment, lack of personalized guidance, and poor user adherence, making it difficult to meet modern public demands for refined and routine dietary health management. Smart diet management software, supported by digital technologies such as artificial intelligence, big data, and computer vision, reconstructs the model of dietary health management and has become an important carrier for popularizing the concept of healthy eating and regulating dietary behavior among the general public. Based on the concept of smart health development, this paper systematically explores the core design logic of public diet management software. It conducts an in-depth analysis of user needs, functional architecture, health-oriented logic, and human-centered design, examines the implementation paths and key points of software interaction design, analyzes existing problems such as homogenization, insufficient practicality, and weak adaptability in current software design and interaction, and proposes optimization strategies. The study aims to provide theoretical reference and practical support for the iterative upgrading of smart diet management products and for empowering public health management.